2014
DOI: 10.1111/myc.12212
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes of invasive fusariosis: review of 65 cases from the PATH Alliance® registry

Abstract: SummaryInvasive Fusarium infections occur in immunosuppressed patients, especially those with haematological malignancies. We conducted a descriptive analysis of data from patients with invasive fusariosis identified in the Prospective Antifungal Therapy Alliance registry, which collected data on invasive fungal infections in the United States and Canada from 2004 to 2008. In this series of 65 patients with proven (83.1%) and probable (16.9%) invasive fusariosis, the most common underlying condition was haemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 19 publications
2
57
2
5
Order By: Relevance
“…The results of imaging studies may reveal suggestive abnormalities in lungs or sinuses and liver or spleen, but reimaging is often necessary after neutrophil recovery because radiologic abnormalities may not be obvious in neutropenic patients [43]. Except for Fusarium , [66] blood culture results are rarely used to diagnose molds. Mold infections are usually confirmed by the study of infected tissue [65].…”
Section: Fungal Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of imaging studies may reveal suggestive abnormalities in lungs or sinuses and liver or spleen, but reimaging is often necessary after neutrophil recovery because radiologic abnormalities may not be obvious in neutropenic patients [43]. Except for Fusarium , [66] blood culture results are rarely used to diagnose molds. Mold infections are usually confirmed by the study of infected tissue [65].…”
Section: Fungal Diagnosticsmentioning
confidence: 99%
“…Fungemia has been estimated to occur in one-third of patients with invasive candidiasis [69] and most of those with disseminated Fusarium [66], but occurs more rarely with molds, such as Aspergillus [70], which may require tissue specimens. The use of automated systems and even rapid identification systems (e.g., peptide nucleic acid fluorescence in situ hybridization/matrix-assisted laser desorption/ionization time-of-flight mass spectrometry [PNA-FISH/MALDI-TOF]) to identify bloodstream yeasts is becoming more widespread [71]; however, traditional characterization by morphologic and biochemical characteristics is still commonly used in LMICs [65, 7274].…”
Section: Fungal Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11, 12, 13, 14, 15, 16 Nucci et al 17 reported 233 cases from different hospitals on a global scale. Mohammed et al 18 reported 26 cases from the United States and reviewed 97 cases from the literature, and Horn et al 12 described 65 cases from the North American Path Alliance Registry. A major problem in comparative studies is the subdivision of the classical species into a series of molecular siblings, which renders the older literature without sequence data uninterpretable.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its resistance to many of the antifungals including AmB, fusariosis treatment is even more complicated [53]. The only data for CAF therapy is a retrospective analysis of patients with invasive fusariosis from the literature.…”
Section: Scedosporium and Fusariummentioning
confidence: 99%